Intravenous prostacyclin-analogue therapy in pulmonary arterial hypertension – A review of the past, present and future. (April 2021) - Stubbe, Beate; Opitz, Christian F.; Halank, Michael; Habedank, Dirk; Ewert, Ralf
Abstract: Therapy with intravenous prostacyclin analogues in patients with pulmonary arterial hypertension (PAH) has been established for decades and is an integral component of the current guidelines for the treatment of pulmonary hypertension. Initially, these drugs were infused by external pump systems via tunnelled right atrial catheters with the need for cooling and frequent exchange of drug reservoirs. Associated complications included, among others, catheter-related infections. More recently, fully implantable pump systems have been developed with drug reservoirs that are filled transcutaneously, allowing intervals between refills of several weeks. This technique results in a low rate of infections. Epoprostenol, iloprost and treprostinil have all been used intravenously in PAH, but titration, dosing and dose escalation in long-term therapy are not standardized. Intravenous prostacyclin analogues are still under-used, despite available data suggesting that early and broad application of these therapies as part of risk-oriented, guideline-directed combination therapy for patients with PAH may lead to a survival benefit. This review provides a detailed overview of the drugs, infusion systems and dosing strategies used for intravenous therapy in patients with PAH. Highlights: Intravenous prostacyclin analogues (PCA) are an established therapeutic option in PAH. PCA application via fully implantable pumps is the current standard of care, while initially external pumps were used. Nevertheless, PCA-titration and dosing in long-term therapy are not standardized. Parenteral PCA-therapy is still underused in PAH despite a potential survival benefit.